The Evaluation of the African Union in Relation to the European Union : comparative analysis - (:unkn) unknown (My University, 2015)
The evaluation of African Unity’s experience in relation to the European Unity exceeds the conceptual aspect as oriented toward a philosophy of mutual interest. Thus, we must recognize that the idea of ​​Union itself was born of a set of historical, political and socioeconomic. This evidence highlights the originality of the European Union who, unlike the African Union, sparked a long awareness of the founding countries, which met at the end of World War II faced with the need to rebuild their country at all levels. Conversely, it seems that little new has been made by the African Union to the Organization of African Unity preexisting. It is clear, moreover, that the African Union has only formally renew the institutional structure of the European Union without taking into account the socio-cultural and politico economic peculiarity of the African continent.
Keywords: African Research